2011
DOI: 10.1128/jvi.01651-10
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Analyses Point to a Polynucleotide-Accommodating Groove Essential for APOBEC3A Restriction Activities

Abstract: Members of the human APOBEC3 family of editing enzymes can inhibit various mobile genetic elements. APOBEC3A (A3A) can block the retrotransposon LINE-1 and the parvovirus adeno-associated virus type 2 (AAV-2) but does not inhibit retroviruses. In contrast, APOBEC3G (A3G) can block retroviruses but has only limited effects on AAV-2 or LINE-1. What dictates this differential target specificity remains largely undefined. Here, we modeled the structure of A3A based on its homology with the C-terminal domain of A3G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
79
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 59 publications
11
79
0
Order By: Relevance
“…Since this history of selection apparently predates the emergence of primate lentiviruses, and the constant rate of selection is inconsistent with the episodic selective pressure that would be applied by an infectious extracellular pathogen, these findings imply that APOBEC3 genes are in conflict with a constant and ancient threat to genomic stability, such as that posed by L1 or other endogenous retrotransposable elements (55). The data from a number of studies support that the overexpression of APOBEC3 proteins in cell lines suppress the retrotransposition of engineered L1 elements (41,42,(56)(57)(58)(59)(60). Different APOBEC3 members exert different levels of suppression with APOBEC3A, -3B, and -3F consistently exhibiting potent effects, whereas APOBEC3G exhibited modest or no activity in the majority of these studies.…”
Section: In Primary Cd4mentioning
confidence: 69%
“…Since this history of selection apparently predates the emergence of primate lentiviruses, and the constant rate of selection is inconsistent with the episodic selective pressure that would be applied by an infectious extracellular pathogen, these findings imply that APOBEC3 genes are in conflict with a constant and ancient threat to genomic stability, such as that posed by L1 or other endogenous retrotransposable elements (55). The data from a number of studies support that the overexpression of APOBEC3 proteins in cell lines suppress the retrotransposition of engineered L1 elements (41,42,(56)(57)(58)(59)(60). Different APOBEC3 members exert different levels of suppression with APOBEC3A, -3B, and -3F consistently exhibiting potent effects, whereas APOBEC3G exhibited modest or no activity in the majority of these studies.…”
Section: In Primary Cd4mentioning
confidence: 69%
“…[27][28][29] Third, researchers have demonstrated that APOBEC3A and other family members have the potential to mediate the clearance of foreign DNA through a deamination-dependent mechanism. [27,30,31] Recent work has also indicated that there are regions of the genome that appear more susceptible to mutation than others. Specifically, late-replicating and heterochromatic regions of the genome appear enriched for mutations when compared to early replicating and euchromatic DNA, respectively.…”
Section: The Apobec Familymentioning
confidence: 99%
“…Although viral DNA integration is an important step in HPV-induced carcinogenesis (24,25), a mechanism of HPV integration remains unknown. A3s can also target DNA viruses that do not use reverse transcription in their replication cycle, including TT virus, adeno-associated virus (AAV), herpes simplex virus 1 (HSV-1), and Epstein-Barr virus (26)(27)(28)(29)(30) (32), raising a concern about whether the observed hypermutation in the transfected HPV DNA truly reflects HPV pathophysiology.…”
mentioning
confidence: 99%